Why Do Patients Derogate Physicians Who Use a Computer-Based Diagnostic Support System?. (January 2013) - Shaffer, Victoria A.; Probst, C. Adam; Merkle, Edgar C.; Arkes, Hal R.; Medow, Mitchell A.
Objective . To better understand 1) why patients have a negative perception of the use of computerized clinical decision support systems (CDSSs) and 2) what contributes to the documented heterogeneity in the evaluations of physicians who use a CDSS.Methods . Three vignette-based studies examined whether negative perceptions stemmed directly from the use of a computerized decision aid or the need to seek external advice more broadly (experiment 1) and investigated the contributing role of 2 individual difference measures, attitudes toward statistics (ATS; experiment 2) and the Multidimensional Health Locus of Control Scale (MHLC; experiment 3), to these findings.Results . A physician described as making an unaided diagnosis was rated significantly more positively on a number of attributes than a physician using a computerized decision aid but not a physician who sought the advice of an expert colleague (experiment 1). ATS were unrelated to perceptions of decision aid use (experiment 2); however, greater internal locus of control was associated with more positive feelings about unaided care and more negative feelings about care when a decision aid was used (experiment 3).Conclusion . Negative perceptions of computerized decision aid use may not be a product of the need to seek external advice more generally but may instead be specific to the use of a nonhuman tool and may be associated with individual differences in locus of control. Together, these 3 studies may be used to guide education efforts for patients.